Barriers to dispatcher-assisted cardiopulmonary resuscitation in Thailand - Tippayanate, Nantawan; Phonkanya, Patchalee; Neungkantee, Kanokwan; Neungkantee, Kamonchanok; Raksapakdee, Kwansiri; Boonnop, Watcharaporn; Jitsuwan, Natlada (International Journal Of Community Medicine And Public Health, 2024)
Background: Dispatcher-assisted cardiopulmonary resuscitation (DA-CPR) has proven effective in boosting bystander CPR rates in out-of-hospital cardiac arrests (OHCA). Recently, Thailand has implemented a DA-CPR program. Our objective was to delineate the obstacles to initiating chest compressions by callers. Methods: We reviewed dispatch recordings of OHCA cases received by the ambulance call center from July 2012 to March 2015. Excluding audio recordings of subpar quality, trained evaluators documented the successive stages of the dispatcher's CPR recognition, delivery of CPR instructions, and the caller's execution of CPR. The time required to achieve these milestones was recorded, while barriers hindering chest compressions were identified. Results: Throughout the study period, researchers identified 280 cases of OHCA. Among these cases, it was observed that 134 bystanders declined to administer CPR. Reasons for refusal varied: 25.4% cited difficulty in controlling their emotions, 21.65% encountered challenges accessing the scene, 20.9% refused to perform CPR, 14.9% dropped out of the call, 9.7% did not approach the emergency patient, 5.9% were unable to perform CPR due to physical limitations, and 2.9% faced difficulty moving the emergency patient to the ground floor. Conclusions: Barriers were present in 47.85% correlating with a reduced proportion of CPR initiation and longer delays in CPR initiation.